DEVELOPMENT OF STUDENTS’ EMOTIONAL INTELLIGENCE: CHARACTER MANAGEMENT IN ISLAMIC EDUCATION LEARNING AS AN EFFORT TO PREVENT DEVIANT BEHAVIOR - Yusuf, Syaifulloh; Nur Zaytun Hasanah,; Istiqomah, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract Bullying cases that occur in the world of education can no longer be stopped. This case continues to happen if educational system does not solve the problems that arise today. Islamic Education (PAI) teachers have an essential role in preventing these cases. This study aims to describe student learning process, Islamic education teacher strategies in student learning, Islamic education learning management, and strategy for strengthening student character in preventing deviant behavior. This study was qualitative research. The instruments used were in-depth interviews, observation, and documentation. The data analysis technique was carried out in four stages: data collection, simplification, data presentation, and conclusion drawing. The results of this study indicated that in developing students' emotional intelligence, PAI teachers used several strategies to manage the learning process. In addition, character education for students was done as a solution to prevent deviant behavior. Therefore, developing students' emotional intelligence can also prevent deviant behavior.